Estimation of the Burden of Serious Human Fungal Infections in Malaysia - Velayuthan, Rukumani Devi; Samudi, Chandramathi; Singh, Harvinder Kaur Lakhbeer; Ng, Kee Peng; Shankar, Esaki Muthu; Denning, David William (MDPI, 2018)
Fungal infections (mycoses) are likely to occur more frequently as ever-increasingly sophisticated healthcare systems create greater risk factors. There is a paucity of systematic data on the incidence and prevalence of human fungal infections in Malaysia. We conducted a comprehensive study to estimate the burden of serious fungal infections in Malaysia. Our study showed that recurrent vaginal candidiasis (>4 episodes/year) was the most common of all cases with a diagnosis of candidiasis (n = 501,138). Oesophageal candidiasis (n = 5850) was most predominant among individuals with HIV infection. Candidemia incidence (n = 1533) was estimated in hospitalized individuals, some receiving treatment for cancer (n = 1073), and was detected also in individuals admitted to intensive care units (ICU) (n = 460). In adults with asthma, allergic bronchopulmonary aspergillosis (ABPA) was the second most common respiratory mycoses noticed (n = 30,062) along with severe asthma with fungal sensitization (n = 39,628). Invasive aspergillosis was estimated in 184 cases undergoing anti-cancer treatment and 834 ICU cases. Cryptococcal meningitis was diagnosed in 700 subjects with HIV/AIDS and Pneumocystis jirovecii pneumonitis (PCP) in 1286 subjects with underlying HIV disease. The present study indicates that at least 590,214 of the Malaysian population (1.93%) is affected by a serious fungal infection annually. This problem is serious enough to warrant the further epidemiological studies to estimate the burden of human fungal infections in Malaysia.